Overviews Knowledge and Attitudes of Cattle Farmer Toward Foot and Mouth Disease (FMD) in Kendari City - Fadli Ma’mun Pancar; Yamin Yaddi; Restu Libriani; Titah Aprilia; Fitria Dewi; La Ode Sahaba (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Foot and mouth disease (FMD) is a disease caused by the FMD virus which has an impact of economic losses for farmers with a high morbidity rate. Knowledge and attitude of farmers towards FMD is very important in efforts to control this disease. The Aim of this study was to describe the knowledge and attitudes of farmers towards foot and mouth disease in cattle in Kendari. This research was conducted from September to December 2022 on 40 cattle farmers in the city of Kendari. Methods of data analysis using descriptive statistics univariate analysis. The results of the farmers' knowledge and attitudes towards foot and mouth disease were 62.83% and 64.25%. The relationship between the variables of gender, age, education level had no significant effect on farmer's knowledge and attitudes (P>0.05). Knowledge and attitude of farmers towards foot and mouth disease in Kendari city is in the sufficient category.